Attitude of International Public Law from International Crime & how to combat it - Umran Iessa Hamoud Al-Gobori (Journal of Madenat Alelem University College, 2019)
Crime had been known since the beginning of human beings, since the emergence of the prophet Adam & what was happened between his sons (Cain & Abel), which was the first crime in history, it was meant to show good & evil in the human soul . Over time, human societies took shape across the ages, succession of generations, the emergence & development of human groups . Wars & conflicts were the visible , continuing feature of their poles over the centuries, because of the multiplicity of the interests of these groups. Crime had evolved , developed in human societies, so that it became one of the most prominent features of human history, this had led these groups to form political , legal collocations to reach the so-called political systems ( States ) . With the continuation of conflicts & wars, it appeared that there was an urgent need to find binding rules for belligerents to limit the commission of crimes against humanity as a result of those wars, & the subordination of those conflicts to these norms, inspired by the values , teachings of heaven & humanitarian considerations, as a confirmation of social norms, through these values have been established in the minds of human societies over the time. Which follows the course , development of human life, finds the outbreak of armed & non-armed conflicts that resulted in acts & crimes that have claimed the lives of many human beings. These crimes can be described as international crimes such as terrorist crimes, crimes against humanity, genocide, war crimes, which were committed by those who are influential - traders of war - during those international & non-international armed conflicts . In spite of treaties , agreements concluded within the framework of international, regional organizations & bilateral agreements to limit such crimes, they have not succeeded. Therefore, these crimes continued through gross violations of these conventions, as well as violations of the four Geneva Conventions of 1949, & serious violations of the laws & customs applicable to international disputes under general international law. In any case, the rules of public international law have become rules of control & binding for the maintenance of international peace & security to stand up to those international crimes through the establishment of international criminal tribunals & special tribunals to consider, combat or limit such crimes at the very least. Since the jurisdiction of the International Criminal Court is limited to the most serious crimes under article 5 (a), which defines by crimes of genocide, crimes against humanity, war crimes & crimes of aggression, it disregards other crimes such as terrorist crimes & drug crimes, it is therefore necessary to include such crimes in the jurisdiction of the above-mentioned court, because they have become international crimes with distinction because they threaten security and stability in most countries of the world, or formation of special courts for this purpose.